Card type deoxidizer preparation method and product

Through the preparation method of card type deoxidant, dust problems and slow reaction speeds in the production process of existing iron deoxidants are solved, and efficient deoxidation and clean production are achieved.

CN119817630APending Publication Date: 2025-04-15DONGGUAN XINRONG TIANLI TECH IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510150909.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing iron-based deoxidants produce a large amount of dust during the production process, affecting the health of the operators and product cleanliness. At the same time, the reaction speed of block and rod-shaped deoxidants is slow, resulting in poor deoxidation effect.

Method used

The card type deoxidant preparation method is adopted to make environmentally friendly colloids by mixing polymer powder, purified water and other raw materials, and evenly mixing them with bentonite, short fiber, iron powder, activated carbon and other ingredients. After calendering and hot air dehydration, the card type deoxidant is finally made.

Benefits of technology

It reduces dust generation, improves the cleanliness of the product and the cleanliness of the production environment, and enhances the reaction speed and deoxygenation effect of the deoxidant, extends the shelf life of the food.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005268043050000061
    Figure BDA0005268043050000061
  • Figure BDA0005268043050000071
    Figure BDA0005268043050000071
  • Figure BDA0005268043050000072
    Figure BDA0005268043050000072
Patent Text Reader

Abstract

The invention relates to the technical field of deoxidizer processing, in particular to a card type deoxidizer preparation method and a card type deoxidizer product. The card type deoxidizer preparation method comprises the following preparation steps that S1, high-molecular polymer powder and purified water are mixed, heated in a water bath and stirred to be uniform, and semitransparent environment-friendly colloid is obtained; s2, uniformly stirring the environment-friendly colloid, bentonite and short fibers to obtain a clay material; s3, adding iron powder, activated carbon and syrup into the clay material, and uniformly stirring to obtain a mixture A; s4, placing the mixture A between two layers of release films, repeatedly calendering, and uncovering the upper film after reaching a specified thickness to obtain a wet sheet; s5, the wet sheet is fixed and shaped, complete dehydration treatment is conducted through a hot air process, and a dry sheet is obtained; and S6, the dry sheet is cut, then saline water is used for rewetting treatment, sealing is conducted, and the card type deoxidizer is obtained, effective components such as iron powder and activated carbon are evenly dispersed in a matrix formed by a high-molecular polymer and bentonite, and the deoxidation efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of deoxidizer processing, and more specifically, to a preparation method and product of a card-type deoxidizer. Background Art

[0002] Iron-based deoxidizers use iron powder to react with oxygen and water to generate iron hydroxide to consume oxygen and achieve the purpose of deoxidation. This chemical reaction not only consumes oxygen in the package, but also reduces the oxygen concentration, creating an anaerobic environment for food, thereby effectively slowing down the oxidation process of food and extending the shelf life of food.

[0003] The iron-based deoxidizer exists in the form of powder, block and rod, among which the powdered iron-based deoxidizer is composed of reactants and packaging film. The contents are iron powder, activated carbon, electrolyte solution, etc., which absorb oxygen through the redox reaction between iron and oxygen, so as to remove oxygen in the packaging bag, inhibit the growth and reproduction of aerobic bacteria, and thus extend the shelf life of food. The production process of powdered iron-based deoxidizer products on the market is "pre-stirring the heating powder, and then directly feeding it after standing and cooling". This production method requires that the heating material should not have too much water, the powder must have good fluidity, and the viscosity between the powders should be as small as possible. Generally, silicon dioxide is added to increase the fluidity of the powder and reduce the viscosity between the powders. Therefore, if there is a lot of powder in the formula and the water content is low, a large amount of dust will inevitably be generated during the production process, which will have a great impact on the health of the operators, the cleanliness of the product, and the cleanliness of the production environment.

[0004] Block and rod iron deoxidizers undergo a specific molding process, such as pressing or extrusion, to form a compact block or rod structure. During this process, the raw materials are tightly combined together, reducing the possibility of dust generation. However, compared with powdered deoxidizers, block and rod deoxidizers may react more slowly because their surface area is relatively small, the opportunity to contact with oxygen is limited, and their ability to absorb oxygen is not as good as that of powdered iron deoxidizers, resulting in poor deoxidation effect, so they need to be improved. Summary of the invention

[0005] In order to improve the deoxidation efficiency of a deoxidizer, the present application provides a card-type deoxidizer preparation method and product.

[0006] In the first aspect, the present application provides a method for preparing a card-type deoxidizer, using the following technical solution: A method for preparing a card-type deoxidizer comprises the following preparation steps: S1. Mix high molecular polymer powder and purified water, heat in a water bath, and stir until uniform, to obtain a translucent environmentally friendly colloid; S2. Mix the environmentally friendly colloid, bentonite and short fibers evenly to obtain a clay material; S3, adding iron powder, activated carbon and syrup to the clay material, stirring evenly to obtain a mixture A; S4, placing the mixture A between two release films, and then passing through several rollers, repeatedly rolling until the specified thickness is reached, and then peeling off the upper film to obtain a wet sheet; S5, fixing and shaping the wet sheet, and completely dehydrating the wet sheet by hot air process to obtain a dry sheet; S6. Cut the dry sheet, rewet it with salt water, and seal it to obtain a card-type deoxidizer.

[0007] By mixing raw materials such as polymer powder and purified water to form an environmentally friendly colloid, and evenly mixing it with other ingredients such as bentonite, short fibers, iron powder, activated carbon, and syrup, and then undergoing processes such as calendering and shaping, the final result is a card-shaped deoxidizer. Compared with the powdered deoxidizer, this preparation method forms a translucent environmentally friendly colloid by mixing the raw materials, and finally makes a card-shaped deoxidizer through processes such as calendering and dehydration. In this process, the raw materials are closely combined together, reducing the generation of dust, making it possible to produce the deoxidizer in a dust-free environment, which is beneficial to protecting the health of the operators, and also improving the cleanliness of the product and the cleanliness of the production environment. At the same time, through repeated calendering and hot air dehydration treatment, the deoxidizer has a certain strength and toughness, and can maintain a stable deoxidation effect during use. After cutting, the dry sheet is treated with salt water rewetting, which helps the deoxidizer to better contact with the oxygen and water vapor in the package when in use, thereby improving the deoxidation effect. At the same time, the salt water rewetting treatment can also increase the flexibility and toughness of the deoxidizer, making it less likely to break during use, greatly improving its safety as a food contact material. At the same time, the card-type deoxidizer is more conducive to preventing accidental ingestion.

[0008] The card-type deoxidizer is thin and easily deformed and damaged during use. In this application, the card-type deoxidizer is formed into a sheet with a certain thickness and surface area by mixing and calendering raw materials such as polymer powder, bentonite, and short fibers. Such a design increases the chance of the deoxidizer contacting oxygen, thereby improving the deoxidation effect.

[0009] In the present application, the syrup is added in step S3 to improve the forming rate of the wet sheet and ensure the structural stability of the wet sheet. Furthermore, the mass concentration of the syrup is higher than 80%, and it has sufficient viscosity and consistency, which is conducive to the combination of iron powder, activated carbon and clay material, and improves the structural stability of the wet sheet. In the present application, while utilizing the viscosity of the syrup, the syrup is also safe and non-toxic, and is highly safe for preparing a card-type deoxidizer.

[0010] Finally, the card-type deoxidizer has a fixed shape and size, which is convenient for packaging, use and storage. Compared with traditional powder, block or stick deoxidizers, the card-type deoxidizer is easier to control the dosage and placement, thereby improving the convenience and accuracy of use.

[0011] Among them, step S1 mixes the polymer powder with purified water, heats and stirs in a water bath to obtain a translucent environmentally friendly colloid. The purpose of this step is to provide a uniform and viscous carrier for the subsequent mixture. In step S2, the environmentally friendly colloid is evenly mixed with bentonite, short fibers, etc. to obtain a clay material. The clay material has a certain viscosity and plasticity, which provides a good basis for the subsequent addition of effective ingredients such as iron powder. In step S3, effective ingredients such as iron powder and activated carbon are added to the clay material and stirred evenly. Iron powder is the main component of the deoxidizer, which undergoes a redox reaction with oxygen; activated carbon plays an adsorption and catalytic role. In step S4, the mixture is placed between two layers of release films, and the specified thickness is reached through a calendering process, and then the upper film is removed to obtain a wet sheet. The wet sheet is then fixed and shaped, and dehydrated through a hot air process to obtain a dry sheet. The purpose of this step is to solidify the mixture into a card-type deoxidizer with a certain strength and stability.

[0012] Preferably, the weight parts of the raw materials used to prepare the card-type deoxidizer are as follows: 32-50 parts of polymer powder Purified water 100-142 parts 12-25 parts of bentonite Short fiber 15-30 parts Activated carbon 18-32 parts Iron powder 90-150 parts 2-4 parts salt water.

[0013] By adopting the above technical solution, the weight of the raw materials used to prepare the card-type deoxidizer is optimized, the deoxidation effect of the card-type deoxidizer is improved, and the stability and plasticity of the card-type deoxidizer structure are improved, so that it is not easy to be damaged or deformed during use.

[0014] Preferably, the short fibers are modified short fibers, which are prepared by the following method: A: Mix the short fibers and ethanol solution, stir at 100-120r / min, adjust the pH value to 8-9 with ammonia water, heat to 50-60℃, add titanate coupling agent and ethyl cellulose, and keep warm for 60-80min; B: After the heat preservation is completed, the mixture is cooled to room temperature and filtered. The filter cake is washed with anhydrous ethanol and deionized water respectively, and then dried in a drying oven at 100-105°C to constant weight to obtain modified staple fibers.

[0015] By adopting the above technical solution, the overall strength and toughness of the card-type deoxidizer are further enhanced, while helping to improve the air permeability and moisture retention of the deoxidizer, so that the deoxidizer can better contact with the oxygen and water vapor in the package, accelerate the deoxidation reaction, and improve the deoxidation effect.

[0016] Through the steps of mixing ethanol solution, adjusting pH value with ammonia water, adding titanate coupling agent and ethyl cellulose by heating, the surface of the short fiber is effectively modified, so that it is more closely combined with other raw materials (such as polymer powder, bentonite, iron powder, etc.), thereby improving the structural stability of the deoxidizer during use. At the same time, the modified short fiber has better fluidity and plasticity, which makes the card-type deoxidizer easier to shape and process during the production process. At the same time, the strengthening effect of the short fiber also makes the deoxidizer less likely to be damaged or deformed during subsequent processing such as cutting and tailoring.

[0017] Preferably, the weight parts of the raw materials used to prepare the modified staple fibers are as follows: Short fiber 15-30 parts 20-40 parts of ethanol solution 4-8 parts of ammonia water Titanate coupling agent 2-3 parts Ethyl cellulose 2-4 parts.

[0018] By adopting the above technical solution, the weight of the raw materials used to prepare the modified short fibers is optimized, the bonding force between the short fibers and substrates such as polymer powder is further improved, and the card-type deoxidizer has higher physical strength and toughness, and can better resist external impact and wear. At the same time, the dispersibility of the short fibers is further improved, and the contact area between the deoxidizer and the oxygen in the package is increased, thereby improving the deoxidation efficiency. At the same time, the strengthening effect of the short fibers may also make the oxygen diffusion path inside the deoxidizer more complicated, prolonging the reaction time between oxygen and the deoxidation component, and further improving the deoxidation effect.

[0019] Preferably, the bentonite is pretreated before step S2, the steps are as follows: The bentonite is crushed and passed through a 300-500 mesh sieve, then added into the sodium salt solution, stirred for 1-2 hours, filtered, the filter residue is taken, and dried to obtain the pre-treated bentonite.

[0020] By crushing bentonite to 300-500 mesh, its particle size is reduced and the specific surface area is increased, thereby improving its dispersibility in the deoxidizer, which helps the bentonite to mix more fully with other raw materials and form a more uniform structure. At the same time, adding sodium salt solution and stirring for 1-2 hours can change the charge properties on the surface of bentonite, improving its compatibility and reactivity with other components in the deoxidizer. The pretreated bentonite plays a better skeleton support role in the deoxidizer, enhancing the physical strength and toughness of the deoxidizer. At the same time, bentonite has good water absorption and expansion, can absorb and retain a certain amount of water, and helps maintain the stability and durability of the deoxidizer.

[0021] Preferably, the sodium salt solution is obtained by mixing sodium sulfite, sodium acetate and purified water in a weight ratio of 2:3:(8-10).

[0022] By adopting the above technical solution, the activity of bentonite can be further activated, and it can be better combined with deoxidizing components such as iron powder and activated carbon to form a more efficient deoxidation system, thereby improving the deoxidation efficiency. At the same time, sodium sulfite, as a reducing agent, can react with oxygen, thereby consuming oxygen in the package and creating a more hypoxic environment for food. Sodium acetate, as a buffer, can maintain the acid-base balance inside the deoxidizer to prevent the deoxidation effect from being affected by changes in pH.

[0023] Preferably, the polymer powder comprises at least one of starch colloid, xanthan gum or polylactic acid glycolic acid. Starch colloid, xanthan gum or polylactic acid glycolic acid has good adhesion and film-forming properties and can form a stable film in the deoxidizer, tightly combining raw materials such as modified short fibers, bentonite and iron powder, thereby enhancing the overall structural strength of the deoxidizer. This stable structure helps prevent the deoxidizer from breaking or stratifying during use, ensuring its long-term effectiveness.

[0024] Preferably, the short fibers are obtained by mixing short fibers A and short fibers B at a weight ratio of 1:(0.8-1.2); the short fibers A are at least one of wood fibers, polylactic acid fibers or seaweed fibers; B short fiber is viscose fiber.

[0025] A short fiber usually has good biodegradability, hygroscopicity and strength, while B short fiber (viscose fiber) has good flexibility and processability. By optimizing the ratio of the two, a more balanced and stable deoxidizer structure can be formed, thereby improving its overall performance.

[0026] Preferably, the average particle size of the activated carbon is 100-300 nm.

[0027] By adopting the above technical solution, the average particle size of activated carbon is optimized, which helps to form a more compact and uniform structure and enhance the overall stability of the deoxidizer. At the same time, during the preparation and use process, activated carbon particles with smaller particle sizes are less likely to wear and break, thereby extending the service life of the deoxidizer. It also ensures that the card-type deoxidizer has a good deoxidation rate.

[0028] In the first aspect, the present application provides a card-type deoxidizer, which adopts the following technical solution: A card-type deoxidizer, wherein the thickness of the card-type deoxidizer is 0.5-1.5 mm.

[0029] By adopting the above technical solution and optimizing the thickness of the card-type deoxidizer, it can respond more quickly to changes in oxygen concentration inside the package, quickly absorb and remove oxygen, and effectively extend the shelf life of food. At the same time, since the deoxidizer layer is thinner, the overall weight is reduced, which helps to reduce transportation costs.

[0030] In summary, this application has the following beneficial effects: 1. High deoxidation efficiency: The card-type deoxidizer uses a specific preparation process to evenly disperse effective ingredients such as iron powder and activated carbon in a matrix formed by high molecular polymer and bentonite, increasing the contact area with oxygen and thus improving the deoxidation efficiency.

[0031] 2. Dust control: Compared with powdered deoxidizers, card-type deoxidizers do not generate a lot of dust during production and use, which is beneficial to protecting the health of operators and maintaining the cleanliness of products and the cleanliness of the production environment.

[0032] 3. Enhanced mechanical properties: The combination of high molecular polymer, bentonite and short fibers makes the card-type deoxidizer have good mechanical properties, such as toughness, strength and tear resistance. It is not easy to be damaged during use and is easy to cut and pack, which improves the practicality and durability of the product. DETAILED DESCRIPTION Example

[0033] The wood fiber was purchased from Changzhou Longheng Building Materials Technology Co., Ltd. and the grade was industrial A.

[0034] Starch colloid was purchased from Changzhou Longheng Building Materials Technology Co., Ltd. with a relative molecular mass of 600.

[0035] Viscose fiber was purchased from Shandong Fuhui Textile Technology Co., Ltd. with a wet breaking strength of 1.05CN / dtex.

[0036] Example 1 A card-type deoxidizer is prepared by the following method: S1. Mix 320 g of high molecular polymer powder (starch colloid) and 1000 g of purified water, heat in a water bath, and stir to obtain a translucent environmentally friendly colloid; S2. Mix the environmentally friendly colloid, 120 g of bentonite and 150 g of short fibers (wood fibers) to obtain a clay material; S3, add 900g of iron powder, 180g of activated carbon (average particle size of 100-150nm), and 320g of syrup (mass fraction of 80%) to the clay material, stir evenly, and obtain a mixture A; S4, placing the mixture A between two release films, and then passing through several rollers, repeatedly rolling until the specified thickness is reached, and then peeling off the upper film to obtain a wet sheet; S5, the wet sheet is fixed and shaped, and completely dehydrated by hot air process, the hot air temperature is 80-120°C in gradient, the interval is 10°C, the drying time at each temperature is 5 minutes, the wind speed is 3m / s, and a dry sheet is obtained; S6. Cut the dry sheet, rewet it with salt water, and seal it to obtain a card-type deoxidizer with a thickness of 0.5 mm.

[0037] The concentration of the brine is 7%, and the brine accounts for 20% of the wet card-type deoxidizer after the brine is re-wetted.

[0038] The difference between Example 2-3 and Example 1 is that the types and amounts of raw materials used to prepare the card-type deoxidizer and the experimental parameters are different. The specific differences are shown in Table 1: Table 1 Types and amounts of raw materials and experimental parameters for preparing card-type deoxidizers in Examples 1-3 Example 4 A card-type deoxidizer, the difference between this embodiment and embodiment 1 is that the short fiber is a modified short fiber, which is prepared by the following method: A: 150 g of short fibers (wood fibers) and 200 g of ethanol solution (volume concentration of 50%) were mixed and stirred at 100 r / min, and then the pH value was adjusted to 8 with ammonia water, and then the temperature was raised to 50°C, and 20 g of titanate coupling agent and 20 g of ethyl cellulose were added, and the temperature was kept for 60 min; B: After the insulation is completed, the mixture is cooled to room temperature and filtered. The filter cake is washed with anhydrous ethanol and deionized water respectively, and then dried in a drying oven at 105°C to constant weight to obtain modified staple fibers.

[0039] The difference between Example 5-6 and Example 4 is that the types and amounts of raw materials used to prepare the modified staple fibers and the experimental parameters are different. The specific differences are shown in Table 2: Table 2 Types and amounts of raw materials and experimental parameters for preparing modified short fibers in Examples 4-6 Example 7 A card-type deoxidizer, the difference between this embodiment and embodiment 1 is that the bentonite is pretreated before step S2, the steps are as follows: The bentonite was crushed and passed through a 300-mesh sieve, then added into the sodium salt solution, stirred for 1 hour, filtered, and the residue was taken and dried to obtain the pre-treated bentonite.

[0040] The sodium salt solution is obtained by mixing sodium sulfite, sodium acetate and purified water in a weight ratio of 2:3:8.

[0041] Example 8 A card-type deoxidizer, the difference between this embodiment and embodiment 4 is that the bentonite is pretreated before step S2, the steps are as follows: The bentonite was crushed and passed through a 500-mesh sieve, then added into the sodium salt solution, stirred for 2 hours, filtered, the filter residue was taken, and dried to obtain the pre-treated bentonite.

[0042] The sodium salt solution is obtained by mixing sodium sulfite, sodium acetate and purified water in a weight ratio of 2:3:10.

[0043] Example 9 A card-type deoxidizer, the difference between this embodiment and embodiment 1 is that the short fibers are obtained by mixing short fibers A and short fibers B at a weight ratio of 1:0.8; A short fiber is wood fiber; B short fiber is viscose fiber.

[0044] Example 10 A card-type deoxidizer, the difference between this embodiment and embodiment 8 is that the short fibers are obtained by mixing short fibers A and short fibers B in a weight ratio of 1:1; A short fiber is wood fiber; B short fiber is viscose fiber.

[0045] Comparative Example Comparative Example 1 A card-type deoxidizer, this comparative example is different from Example 1 in that no dehydration treatment is performed in step S5.

[0046] Comparative Example 2 A card-type deoxidizer. The difference between this comparative example and Example 1 is that silicon dioxide is used instead of activated carbon.

[0047] Comparative Example 3 A card-type deoxidizer. The difference between this comparative example and Example 1 is that silica is used instead of short fibers.

[0048] Comparative Example 4 A card-type deoxidizer. The difference between this comparative example and Example 1 is that magnesium oxide is used instead of bentonite.

[0049] Comparative Example 5 A card-type deoxidizer, the difference between this comparative example and Example 1 is that pure water is used instead of salt water in step S6.

[0050] Comparative Example 6 A card-type deoxidizer, the difference between this comparative example and Example 1 is that no syrup is added in step S3.

[0051] Performance testing The actual total oxygen absorption amount, oxygen absorption speed, oxygen concentration in the sealed package and structural stability of the card-type deoxidizers prepared in the examples and preparation examples were tested.

[0052] Detection method / test method Actual total oxygen absorption, oxygen absorption speed and oxygen concentration in sealed packaging: According to GB / T 41896-2022 Quality Requirements for Food Deoxidizers, use white oil as the medium. Prepare a 25mm×30mm×1.5mm wet card, use the industry's common dust-proof film packaging for a card-type deoxidizer with a size of 35mm×40mm and a total weight of 1.4±0.1g.

[0053] Structural stability test: Weigh the prepared 25mm×30mm×1.5mm wet card, place it in a rocking machine, rock it for 1 minute, take out the wet card, weigh it again, and calculate the weight change of the wet card. The experimental data is shown in Table 3: Table 3 Experimental data of Examples 1-10 and Comparative Examples 1-5 By comparing Example 1 with Comparative Example 1, the actual total oxygen absorption amount and oxygen absorption rate in Comparative Example 1 are not as good as those in Example 1, the oxygen concentration in the sealed package is greater than that in Example 1, and the weight change after the structural stability test is greater than that in Example 1, indicating that the deoxygenation effect and structural stability of the card-type deoxidizer can be improved through complete dehydration treatment.

[0054] By comparing Example 1 with Comparative Example 1, the actual total oxygen absorption amount and oxygen absorption rate in Comparative Examples 2-4 are not as good as those in the example, the oxygen concentration in the sealed package is greater than that in Example 1, and the weight change after the structural stability test is greater than that in Example 1, indicating that the deoxidation effect and structural stability of the card-type deoxidizer can be improved by using activated carbon, short fibers and bentonite in combination with other raw materials.

[0055] By comparing Example 1 with Comparative Example 5, the actual total oxygen absorption amount and oxygen absorption speed in Comparative Example 5 are not as good as those in Example 1, the oxygen concentration in the sealed package is greater than that in Example 1, and the weight change after the structural stability test is greater than that in Example 1, indicating that the deoxygenation effect and structural stability of the card-type deoxidizer can be improved by salt water rehumidification treatment.

[0056] By comparing Example 1 with Comparative Example 6, the weight change of Comparative Example 6 after the structural stability test is greater than that of Example 1, indicating that the deoxidation effect and structural stability of the card-type deoxidizer can be improved by adding syrup.

[0057] Comparing Example 1 with Examples 4-6, the actual total oxygen absorption amount and oxygen absorption rate in Examples 4-6 are greater than those in the examples, the oxygen concentration in the sealed package is lower than that in Example 1, and the weight change after the structural stability test is greater than that in Example 1, indicating that the modified short fibers obtained by the preparation method in this application can improve the deoxidation effect and structural stability of the card-type deoxidizer.

[0058] By comparing Example 1 with Example 7, the actual total oxygen absorption amount and oxygen absorption speed in Example 7 are greater than those in Example 1, the oxygen concentration in the sealed package is less than that in Example 1, and the weight change after the structural stability test is greater than that in Example 1; By comparing Example 4 with Example 8, the actual total oxygen absorption amount and oxygen absorption speed in Example 8 are greater than those in Example 4, the oxygen concentration in the sealed package is less than that in Example 4, and the weight change after the structural stability test is greater than that in Example 4; It can be seen from the experimental results of Examples 1 and 7, 4 and 8 that the deoxidation effect and structural stability of the card-type deoxidizer can be improved by pretreating the bentonite.

[0059] Comparing Example 1 with Example 9, the actual total oxygen absorption amount and oxygen absorption speed in Example 9 are both greater than those in Example 1, the oxygen concentration in the sealed package is lower than that in Example 1, and the weight change after the structural stability test is greater than that in Example 8; comparing Example 8 with Example 10, the actual total oxygen absorption amount and oxygen absorption speed in Example 10 are both greater than those in Example 8, the oxygen concentration in the sealed package is lower than that in Example 8, and the weight change after the structural stability test is greater than that in Example 8; It can be seen from the experimental results of Examples 1, 9, 8 and 10 that the deoxidation effect and structural stability of the card-type deoxidizer can be improved by mixing wood fiber and viscose.

[0060] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a card-type deoxidizer, characterized in that: The method comprises the following preparation steps: S1. Mix high molecular polymer powder and purified water, heat in a water bath, and stir until uniform, to obtain a translucent environmentally friendly colloid; S2. Mix the environmentally friendly colloid, bentonite and short fibers evenly to obtain a clay material; S3, adding iron powder, activated carbon and syrup to the clay material, stirring evenly to obtain a mixture A; S4, placing the mixture A between two release films, and then passing through several rollers, repeatedly rolling until the specified thickness is reached, and then peeling off the upper film to obtain a wet sheet; S5, fixing and shaping the wet sheet, and completely dehydrating the wet sheet by hot air process to obtain a dry sheet; S6. Cut the dry sheet, rewet it with salt water, and seal it to obtain a card-type deoxidizer.

2. The method for preparing a card-type deoxidizer according to claim 1, characterized in that: The weight parts of the raw materials used to prepare the card type deoxidizer are as follows: 32-50 parts of polymer powder Purified water 100-142 parts 12-25 parts of bentonite Short fiber 15-30 parts Iron powder 90-150 parts Activated carbon 18-32 parts 32-50 parts of syrup.

3. A method for preparing a card-type deoxidizer according to claim 2, characterized in that: The short fibers are modified short fibers, which are prepared by the following method: A: Mix the short fibers and ethanol solution, stir at 100-120r / min, adjust the pH value to 8-9 with ammonia water, heat to 50-60℃, add titanate coupling agent and ethyl cellulose, and keep warm for 60-80min; B: After the heat preservation is completed, the mixture is cooled to room temperature and filtered. The filter cake is washed with anhydrous ethanol and deionized water respectively, and then dried in a drying oven at 100-105°C to constant weight to obtain modified staple fibers.

4. The method for preparing a card-type deoxidizer according to claim 1, characterized in that: The weight parts of the raw materials used to prepare the modified staple fibers are as follows: Short fiber 15-30 parts 20-40 parts of ethanol solution 4-8 parts of ammonia water Titanate coupling agent 2-3 parts 2-4 parts of ethyl cellulose.

5. A method for preparing a card-type deoxidizer according to claim 4, characterized in that: Before step S2, the bentonite is pretreated, the steps are as follows: The bentonite is crushed and passed through a 300-500 mesh sieve, then added into the sodium salt solution, stirred for 1-2 hours, filtered, the filter residue is taken, and dried to obtain the pre-treated bentonite.

6. A method for preparing a card-type deoxidizer according to claim 4, characterized in that: The sodium salt solution is obtained by mixing sodium sulfite, sodium acetate and purified water in a weight ratio of 2:3:(8-10).

7. The method for preparing a card-type deoxidizer according to claim 1, characterized in that: The high molecular polymer powder includes at least one of starch colloid, xanthan gum or polylactic acid and glycolic acid.

8. The method for preparing a card-type deoxidizer according to claim 1, characterized in that: The short fibers are obtained by mixing short fibers A and short fibers B in a weight ratio of 1:(0.8-1.2); A short fiber is at least one of wood fiber, polylactic acid fiber or seaweed fiber; B short fiber is viscose fiber.

9. The method for preparing a card-type deoxidizer according to claim 1, characterized in that: The average particle size of the activated carbon is 100-300 nm.

10. A product obtained by the method for preparing a card-type deoxidizer according to any one of claims 1 to 9, characterized in that: The thickness of the card type deoxidizer is 0.5-1.5mm.